Evaluation of the distribution pattern on a Neotropical microcarnivora - Rodríguez-Ruiz, Rodolfo; Juárez-Agis, Alejandro; García Sánchez, Silberio; Olivier Salome, Branly; Reza Galicia, Víctor Hugo (THERYA, 2022)
The Pacific region, one of the most disturbed areas in México, is home to the pygmy spotted skunk (Spilogale pygmaea), a local endemic species and one of the smallest carnivores in the world. This small carnivore is currently listed as a species subjected to special protection in México and the International Union for Conservation of Nature. The objective of this work was to model environmental suitability and estimate the potential distribution of S. pygmaea in México. Predictive models were created using climatic, anthropic, and topographic variables with the Maxent tool. Models were assessed through partial Receiver Operating Characteristic (ROC) performance by omission rate and AUC. Finally, land use within the predicted potential area (potential distribution) was analyzed using the 2015 land cover layer of México issued by CONABIO. According to the model, S. pygmaea has a potential distribution from southern Sinaloa to Chiapas, comprising Michoacán and Guerrero towards the Balsas River basin in relation to dry forests. The predicted area was 95,600 Â± 0.02 km2, representing a restricted distribution in México. Many localities have low environmental suitability (<0.4) and ecosystem modification and fragmentation, mainly influenced by livestock density. Spilogale pygmaea may be considered rare due to the lack of sampling, which jeopardizes the conservation of this group given its fragmented habitat. Additionally, S. pygmaea is attracted to areas with human settlements, potentially leading to human-animal conflicts. Natural areas, along with information sharing on the presence and importance of the species in nearby communities, may be an effective strategy to benefit this small carnivore.